Regional metamorphism of pelites and calc-silicate rocks in the area north of Ravne na Koroškem - Hinterlechner-Ravnik, Ana (Geologija, 1984)
During the prograde regional metamorphism of the Ravne na Koroškem pelites, the instability of garnet, staurolite, and muscovite led to the development of sillimanite fibrolite after biotite replacing the garnet. Completely preserved garnet crystals, and also complete fibrolite pseudomorphs after idiomorphic garnet are observed. The metamorphic grade of scarce calc-silicate intercalations corresponds to the one observed in metapelites. For the metamorphic area are characteristic many pegmatitic veins of leucogranitic composition. They may be considered Products of the anatexis of gneisses at the very beginning of the sillimanite metamorphic field observed in the adjacent schist and gneiss.